2018
DOI: 10.5152/tjg.2018.17627
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange for hypertriglyceridemia induced acut pancreatitis: the 33 cases experience from a tertiary reference center in Turkey

Abstract: Background/Aims: Hypertriglyceridemia (HTG) is the third most common cause of acute pancreatitis. In patients with severe HTG (TG level>1000 mg/dL), it may be beneficial to immediately lower the levels of triglyceride (TG) and chylomicrons. In this study, we present one of the largest case series on the use of therapeutic plasma exchange (TPE) for hypertriglyceridemia-induced acute pancreatitis (HTG-AP). Materials and Methods: Overall, 33 patients who were admitted to our clinic for HTG-AP and underwent TPE be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 33 publications
3
19
2
3
Order By: Relevance
“…This is a safe, effective, and inexpensive first‐line therapy for hypertriglyceridemia‐associated AP. Plasmapheresis can be used to clear the triglycerides, which has been described as a treatment option for hypertriglyceridemia‐induced AP with early therapy associated with improved outcomes 41 . The six patients reported in this study have received insulin, DKA therapy, and plasmapheresis that helped control their symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a safe, effective, and inexpensive first‐line therapy for hypertriglyceridemia‐associated AP. Plasmapheresis can be used to clear the triglycerides, which has been described as a treatment option for hypertriglyceridemia‐induced AP with early therapy associated with improved outcomes 41 . The six patients reported in this study have received insulin, DKA therapy, and plasmapheresis that helped control their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmapheresis can be used to clear the triglycerides, which has been described as a treatment option for hypertriglyceridemia-induced AP with early therapy associated with improved outcomes. 41 The six patients reported in this study have received insulin, DKA therapy, and plasmapheresis that helped control their symptoms. Previous studies have used insulin and hydration therapy in nine patients, but only three patients (3/9) underwent plasmapheresis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies are sparse. Plasma exchange and DFPP have also been found to be safe and effective for the emergency treatment of severe HTG-AP during pregnancy [6,[18][19][20][21][22][23][24][25][26][27][28]. Shortening of hospitalization was reported as a major benefit [23,29].…”
Section: Htg-apmentioning
confidence: 99%
“…Criteria. Inclusion criteria were as follows: (1) The time from onset to hospital admission is less than 48 h, and the medical history, clinical manifestations, serological indicators, and CT examination of the upper abdomen all meet the relevant diagnostic criteria of the Chinese Guidelines for the Diagnosis and Treatment of Acute Pancreatitis (2014 Edition). (2) The patient is diagnosed with hyperlipidemia: TG > 11:3 mmol/l or TG of 5.65~11.3 mmol/l, and the serum is chylous.…”
Section: Inclusion Criteria and Exclusionmentioning
confidence: 99%
“…According to statistics, the incidence of hypertriglyceridemia in the social population is increasing year by year, and the diseased population is showing a younger trend. The disorder of primary or secondary lipoprotein metabolism structure further leads to the occurrence of acute pancreatitis, which becomes an important pathogenic factor after stones and alcohol consumption [1]. It is reported that the incidence of pancreatitis in patients with hypertriglyceridemia accounts for about 15% to 20% [2].…”
Section: Introductionmentioning
confidence: 99%